1997
DOI: 10.1093/carcin/18.11.2163
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of black tea on the growth of established skin tumors in mice: effects on tumor size, apoptosis, mitosis and bromodeoxyuridine incorporation into DNA

Abstract: Female CD-1 mice were initiated with a single topical application of 7,12-dimethylbenz[a]anthracene and promoted with 12-O-tetradecanoylphorbol-13-acetate. Mice with established papillomas were then treated with black tea or decaffeinated black tea (approximately 4 mg tea solids/ml) as the sole source of drinking fluid for 11-15 weeks. In four separate experiments, oral administration of black tea inhibited the growth of papillomas (increase in tumor volume/mouse) by an average of 35%, 37%, 41% and 48%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 6 publications
1
46
0
Order By: Relevance
“…PCNA, a subunit of DNA polymerase, plays a crucial role in DNA replication and repair and serves as a biomarker of proliferation (22). Earlier studies have reported that inhibition of DNA synthesis and cell proliferation by black tea, green tea, caffeine, or epigallocatechin is associated with their cancer chemopreventive efficacy (7,23). Silibinin also inhibited UVB-induced DNA synthesis and cell proliferation, as observed by a decrease in BrdUrd incorporation and PCNA-positive cells in uninvolved skin and tumors, suggesting a plausible role of in vivo antiproliferative effect of silibinin in its overall efficacy against UVB-induced tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA, a subunit of DNA polymerase, plays a crucial role in DNA replication and repair and serves as a biomarker of proliferation (22). Earlier studies have reported that inhibition of DNA synthesis and cell proliferation by black tea, green tea, caffeine, or epigallocatechin is associated with their cancer chemopreventive efficacy (7,23). Silibinin also inhibited UVB-induced DNA synthesis and cell proliferation, as observed by a decrease in BrdUrd incorporation and PCNA-positive cells in uninvolved skin and tumors, suggesting a plausible role of in vivo antiproliferative effect of silibinin in its overall efficacy against UVB-induced tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent laboratory studies have indicated that green tea and its polyphenolic constituents impart inhibitory effects on the activities of many enzymatic, metabolic and signaling pathways that have relevance to cancer development and progression (31)(32)(33)(34)(35)(36). A number of studies have shown the growth inhibitory effects of green tea against many animal tumor bioassay systems including lung, skin and forestomach (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have demonstrated that topical application or ingestion ofgreen tea polyphenols or EGCG inhibit tumor initiation and promotion by chemical carcinogens and UV light in mice [26]- [29]. Black tea has similar effects [29]- [32]. Topical application of a greentea polyphenolic fraction on mice skin papillomas can decrease significantly the conversion of benign tumors tomalignant tumors [33].…”
Section: Health Benefits Of Green and Black Tea 41 Cancer Prevenmentioning
confidence: 99%